Inside Back Cover: A Highly Stable Nonhysteretic Cu2(tebpz) MOF+water Molecular Spring (ChemPhysChem 21/2016). Issue 21 (7th November 2016) - Grosu, Yaroslav; Li, Mian; Peng, Yun‐Lei; Luo, Dong; Li, Dan; Faik, Abdessamad; Nedelec, Jean‐Marie; Grolier, Jean‐Pierre
Abstract : The Inside Back Cover illustrates fascinating properties of a new molecular spring. The spring, formed from a stable hydrophobic metal–organic framework (MOF) Cu2 (tebpz), can store mechanical and thermal energy simultaneously upon intrusion of H2 O molecules into the MOF pores under reasonable operational pressure. More information can be found in the Communication by Y. Grosu and co‐workers onpage 3359 in Issue 21, 2016 (DOI:10.1002/cphc.201600567 ).